Djibouti : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Djibouti. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Djibouti discusses that large-scale infrastructure investments and a rapid expansion of trade and logistics activities have fueled strong growth in recent years. The government has in recent years implemented large-scale investments to develop transport and logistics infrastructures. Combined with business climate reforms, this development strategy has fueled strong growth and positioned Djibouti well to become a regional trade and logistics hub. The IMF staff's baseline projections assume a significant reduction in debt financed public investment. Growth is nonetheless projected to remain strong, driven by the rapid expansion in Ethiopia's trade and a pickup in private investment. Fostering higher and inclusive growth and bolstering the external position require addressing impediments to private sector investment and improving external competitiveness. Critical reforms include further enhancing the business environment, promoting competition, and improving the governance and efficiency of public enterprises to lower factor costs, particularly in the telecommunications and electricity sectors.